2023
DOI: 10.1097/lvt.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for antibody-mediated rejection in ABO blood-type incompatible and donor-specific antibody-positive liver transplantation

Abstract: Antibody-mediated rejection (AMR) is a refractory rejection after ABO blood-type incompatible (ABOi) or donor-specific antibody (DSA)-positive liver transplantation (LT). Pretransplant rituximab desensitization dramatically reduced posttransplant AMR development; however, risk factors for AMR in the rituximab era remain unclear in both ABOi living-donor LT (ABOi-LDLT) and preformed DSA-positive LT (pDSA-LT). Of our 596 adult LDLTs (≥18 y) after rituximab introduction (2004–2019), 136 were ABOi-LDLT (22.8%). Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…However, we never underestimate DSA-related complications. As shown, 1 5 of 10 patients with sum-mean fluorescence intensity ≥10,000 developed AMR with long-lasting high-titer DSAs. Our experience since the 1990s revealed that persistent humoral alloreactivity and its long-term exposure can cause chronic graft fibrosis, 5 which likely affects long-term prognosis.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…However, we never underestimate DSA-related complications. As shown, 1 5 of 10 patients with sum-mean fluorescence intensity ≥10,000 developed AMR with long-lasting high-titer DSAs. Our experience since the 1990s revealed that persistent humoral alloreactivity and its long-term exposure can cause chronic graft fibrosis, 5 which likely affects long-term prognosis.…”
mentioning
confidence: 82%
“…Collectively, ABOi-AMR significantly deteriorated graft/recipient survival, whereas pDSA-AMR, if properly treated, did not significantly affect patient survival with slower/milder onset than ABOi-AMR. [1] A recent large-cohort study also reported no significant impact of pDSAs on post-LT recipient survival. [4] However, we never underestimate DSA-related complications.…”
mentioning
confidence: 95%
See 3 more Smart Citations